Air gap spinning of a cellulose solution in [DBNH][OAc] ionic liquid with a novel vertically arranged spinning bath to simulate a closed loop operation in the Ioncell® process. Issue 5 (24th August 2020) - Guizani, Chamseddine; Larkiala, Sauli; Moriam, Kaniz; Sawada, Daisuke; Elsayed, Sherif; Rantasalo, Sami; Hummel, Michael; Sixta, Herbert
Abstract: A novel, small‐volume vertically arranged spin bath was successfully developed for an air gap lyocell‐type spinning process. A maximum regeneration bath length with a minimum free volume characterizes the concept of the new spin bath. Using the ionic liquid (IL) 1, 5‐diazabicyclo[4.3.0]non‐5‐enium acetate [DBNH][OAc], the spin bath showed very good spinning performances of IL‐cellulose dopes at high draw ratios and spinning duration for single filament spinning experiments. Using this new device, it was possible to get a step further in the optimization of the Ioncell® process and simulate a process closed loop operation by performing single filament spinning in IL/H2 O mixtures. Good dope spinnability and preserved fibers mechanical properties were achieved in a coagulation bath containing up to 30 wt% IL. It is only at 45 wt% of IL in the bath that the spinnability and fibers mechanical properties started to deteriorate. The fibers fibrillar structure was less pronounced in IL‐containing spinning bath in comparison to a pure water bath. However, their crystallinity after washing was preserved regardless of the spinning bath composition. The results presented in this work have a high relevance to the upscaling of emerging IL‐based cellulose dissolution and spinning processes. Abstract :